KEMANFAATAN DAN MAKNA KOSAKATA JAWA KUNO/SANSKERTA DI RUANG PUBLIK - Nardiati, Sri; Riani, NFN (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2023)
Currently, the Javanese Kuno or Sanskrit language has been used to name several government buildings in the Special Region of Yogyakarta. However, the vocabulary is no longer used in daily communication because it is pressed by the use of Javanese, Indonesian, and foreign languages. In fact, the Kuno Javanese language is a cultural heritage that needs to be preserved. For this reason, this study aims to describe the categories, structure, and meaning of Javanese Kuno vocabulary as the name of an institution or institution in DIY. Research data in the form of names of institution/ institutions in the DIY area. Data is collected by photographing and then transliterated. Structural theory with its qualitative approach, distribution method, and technique for direct elements (BUL) is used to analyze data. Based on the results of the analysis, it is known that all names of institutions with elements of classical vocabulary (Javanese, Kuno, and Sanskrit) are categorized as nominal phrases. Elements that are positioned on the far left have the status of being explained, elements that are in the order on the right have the status of explaining, for example Grha Wana Bhakti Yasa. Names in public spaces that use classical vocabulary add at least two elements, such as Sabha Pramana, while the most complex number six elements, such as Kunda Niti Mandala and Tata Sasana. There are three elemental meaning relationships, namely the function meaning relationship, the hope meaning relationship, and the identity meaning relationship. The results of this study can be used as material for determining self-naming policies, implementing conservation, and revitalizing the Kuno Javanese language.Saat ini bahasa Jawa Kuno atau Sanskerta telah dimanfaatkan untuk menamai beberapa gedung pemerintahan di Daerah Istimewa Yogyakarta. Namun, kosakata tersebut tidak lagi digunakan dalam komunikasi sehari-hari karena terdesak oleh penggunaan bahasa Jawa, bahasa Indonesia, dan bahasa asing. Padahal, bahasa Jawa Kuno merupakan warisan budaya yang perlu dilestarikan. Untuk itu, penelitian ini bertujuan mendeskripsikan kategori, struktur, unsur, dan hubungan makna antarunsur kosakata Jawa Kuno sebagai nama Lembaga atau institusi di DIY. Data penelitian berupa nama-nama lembaga/institusi di wilayah DIY. Data dikumpulkan dengan cara difoto kemudian ditransliterasikan. Teori struktural dengan pendekatan kualitatif, metode agih, dan teknik bagi unsur langsung (BUL) digunakan untuk menganalisis data. Berdasarkan hasil analisis diketahui bahwa semua nama lembaga yang berunsur kosakata klasik (bahasa Jawa Kuno dan Sanskerta) berkategori frasa nominal. Unsur yang berposisi di urutan paling kiri berstatus diterangkan, unsur yang berada di urutan sebelah kanan berstatus menerangkan, misalnya Grha Wana Bhakti Yasa. Nama di ruang publik yang menggunakan kosakata klasik sekurang-kurangnya berjumlah dua unsur, misalnya Sabha Pramana, sedangkan yang paling kompleks berjumlah enam unsur, misalnya Kunda Niti Mandala sarta Tata Sasana. Hubungan makna unsurnya ada tiga, yaitu hubungan makna fungsi, hubungan makna harapan, dan hubungan makna identitas. Hasil penelitian ini dapat digunakan sebagai bahan penentuan kebijakan pemberian nama diri, pelaksanaan konservasi, dan revitalisasi bahasa Jawa Kuno.